The Challenge of Military Reform in Postcommunist Europe
X, 260 p. 1 illus.
Keywords: This major comparative study examines the challenges faced by countries of postcommunist Europe in reforming and professionalizing their armed forces. It explores how the interaction of the common challenges of postcommunism and the diverse circumstances of individual countries are shaping professionalization processes in this changing region. The detailed country case studies in this volume, written by leading experts to a common analytical framework, compare the experiences of Poland, the Czech Republic, Slovakia, Hungary, Latvia, Lithuania, Romania, Bulgaria, Slovenia, Croatia, FRY, Russia and Ukraine.